IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DESTINASI WISATA BERBASIS MASYARAKAT KAWASAN WISATA - Nur Asiah; Riwan Laraga (Universitas Bina Taruna Gorontalo, 2024)
This research aims to review and analize how the policy for developing community-based tourist destinations in tourist areas in Bone Bolango Regency is implemented. Bone Bolango Regency is one of the districts that has many land and sea tourism destinations that need to be managed so that they can become strategic economic potential. This research was conducted in 2023 with a qualitative descriptive approach. The sample in this research was taken purposively from elements involved in tourism in Bone Bolango Regency, namely the Head of the Tourism Division, Head of the Tourist Destination Development Section, Village Head of the tourist destination, the community and visitors to the tourist destination. The research results show that Bone Bolango Regency has had various policies issued by the Regional Government aimed at managing tourism affairs and development in the form of Regional Regulations, Regent Regulations, and other decrees as part of policy derivation. Management policies for the development of community-based tourism destinations have been implemented, but they have not yet been implemented optimally. This is because the implementation of this policy is still limited to routine administrative activities.